Strongly Solid Varieties in Many-Sorted Algebras - Chumpungam, Dawan; Leeratanavalee, Sorasak (Communications in Mathematics and Applications, 2018)
In this paper, we apply the general theory of conjugate pairs of additive closure operators to characterize the strongly solid variety which is extended from one-sorted algebras to many-sorted algebras. Moreover, we give the concept of \(V\)-normal form which is useful for testing the strongly solid variety in many-sorted algebra.
Keywords: many-sorted algebra; i-sorted $Σ$-generalized hypersubstitution; i-sorted $Σ$-algebras; $Σ$-terms; $Σ_identity$